Pharmaceuticals, illicit drugs and their metabolites in fish from Argentina: Implications for protected areas influenced by urbanization - Ondarza, Paola Mariana (2019)
Because an understanding of aquatic bioaccumulation of human pharmaceuticals in Latin America is limited, this area was recently identified as a priority environmental quality research need. We examined bioaccumulation of twenty-seven pharmaceuticals, illicit drugs and their metabolites in muscle, liver and gills of multiple fish species (Rhamdia quelen, Hypostomus commersoni, Hoplias lacerdae, Prochilodus lineatus) from an urban river receiving wastewater discharges (Paraná) and a lotic system (Acaraguá) without direct wastewater sources, which runs through a protected area. All samples were analyzed using isotope-dilution liquid chromatography-tandem mass spectrometry. Caffeine, which was detected up to 13 μg/kg, and antibiotics were consistently detected in all fish. Among antibiotics, erythromycin was ubiquitous (0.7–5.6 μg/kg) but its tissue concentrations were lower than levels of sulfamethoxazole, sulfathiazole and trimethoprim (0.9–5.5 μg/kg), which are used in human medicine, aquaculture and livestock. Erythromycin bioaccumulation in fish is reported here from Argentina for the first time, though levels of antibiotics in edible muscles of these species were lower than the maximum residue limits for human consumption. We observed norfluoxetine, the primary active metabolite of the antidepressant fluoxetine, ranging from 1.1–9.1 μg/kg in fish. We further identified benzoylecgonine, a primary metabolite of cocaine, in fish from both study systems, representing the first observation an illicit drug or associated metabolites bioaccumulation in aquatic life from Argentina. Interestingly, high pharmaceutical levels were observed in fish from the Acaraguá river suggesting their transport into the protected area, from the surrounding lands. Though fish from the Paraná river were sampled near WWTP discharges, pharmaceutical concentrations may have been reduced by hydrological and other environmental conditions, and biological differences among species. These findings, which observed bioaccumulation of select pharmaceuticals, their metabolites and illicit drugs in wild fish sampled inside a protected area, highlight the importance of developing an advanced understanding of urban influences on inland protected watersheds.